2006
DOI: 10.1097/01.tp.0000203319.93328.27
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation with Concomitant Unilateral Nephrectomy: A Matched-Pair Analysis on Complications and Outcome

Abstract: Kidney transplantation with concomitant unilateral nephrectomy has no negative impact on patient or graft survival and is associated with a reasonable morbidity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
13
0
2
Order By: Relevance
“…However, these advantages are counterbalanced by the potential for more postoperative complications such as bleeding and infection [16,17]. This may also have an adverse affect on patient as well as graft survival rates after transplantation, but some studies have refuted this observation [7,14,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, these advantages are counterbalanced by the potential for more postoperative complications such as bleeding and infection [16,17]. This may also have an adverse affect on patient as well as graft survival rates after transplantation, but some studies have refuted this observation [7,14,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bilateral nephrectomy simultaneous to transplantation would have the theoretical advantage of reducing the overall number of operative procedures thereby minimizing surgery injury. However, concern has been raised as to whether patients undergoing KT with adjuvant bilateral nephrectomy are at an increased risk for postoperative complications, such as bleeding and infection, which might deteriorate patient and graft survival rates after KT [16] . From the experience of our center, CBN during KT significantly relieved the patients from persistent arterial hypertension and urinary tract infection, although it might increase operation time, blood transfusion and the incidence of adjacent organ injury.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with ABO‐compatible living donor kidney transplantation, there is no difference in surgical techniques and spectrum of surgical complications (as classified in Table ) . However, one study reported a nonsignificant trend to a higher incidence (25%) of immediate postoperative bleeding and a more frequent surgical revision rate .…”
Section: Surgical Complicationsmentioning
confidence: 99%